A Simple Approach for Force Finding Analysis of Suspended-Domes Based on the Superposition Principle. Issue 11 (November 2014) - Guo, J.M.; Yuan, X.F.; Li, Y.Y.; Dong, S.L.
This paper proposes a simple approach for force finding analysis of suspended-domes based on the superposition principle. First, the feasibility of the superposition principle in a suspended-dome during tension is validated using an experimental model and the corresponding numerical model. Following that, a simplified computational method for force finding based on the superposition principle is presented. Taking a suspended-dome as an illustrative example, the initial strain at zero state is calculated by force finding, and the difference between the simplified computational method and the iterative method is investigated. The results show that the superposition principle is nearly feasible during tension and the proposed simple approach is accurate and can easily obtain the actual initial pre-stress of a suspended-dome.